Observational study of the clinical value of the canine osteoarthritis staging tool. (May 2022) - Stabile, M.; Van Ryssen, B.; Minei, S.; Coppieters, E.; Crovace, A.; Lacitignola, L.; Staffieri, F.
Abstract: The aim of this multi-centred, cohort, prospective, observational study was to evaluate the clinical application of the canine osteoarthritis staging tool (COAST), in dogs affected by osteoarthritis (OA). In all dogs, a COAST stage was obtained based on the Liverpool Osteoarthritis in Dogs (LOAD) score and a complete orthopaedic and radiographic examination. The severity of OA (COAST stage) was scored as 1 (preclinical), 2 (mild), 3 (moderate), and 4 (severe). These scores were compared with the overall subjective opinion of experienced orthopaedic surgeons who examined the dogs (Clinical Opinion). Data were analysed with descriptive statistic, multiple regression analysis, chi-square and Bland-Altman tests ( P < 0.05). In total, 362 evaluations were performed in 202 dogs. Clinical Opinion had a greater proportion of stage 1 and 2 cases compared to COAST ( P < 0.0001). The proportion of stage 4 cases was higher in COAST compared to Clinical Opinion ( P < 0.0001). The proportions of Stage 3 cases were similar in the two evaluation systems. COAST had a strong correlation ( r = 0.79; P < 0.01) with Clinical Opinion. Overall, the two evaluation systems exhibited strong agreement (mean bias 0.51). Stages 1 and 2 had weaker agreement (mean bias 1.04 and 0.75, respectively), than stage 3 and stage 4 (mean bias 0.46 and 0.0, respectively). Highlights: Osteoarthritis causes pain and reduction of mobility and quality of life in dogs. The Canine Osteoarthritis Staging Tool (COAST) was valid for staging OA in dogs. The COAST correlated well with the veterinarian's clinical assessment of OA. This tool includes owner input, thereby improved diagnosis of early-stage OA.